(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The use and disposal of electronic devices around the world are constantly increasing. Due to this, electronic waste (e-waste) has quickly become a major environmental and public health issue. Improperly handled e-waste can be very dangerous to soil, water, air quality, and human health because it contains dangerous chemicals like lead, mercury, cadmium, and brominated flame retardants. An increasingly appealing aspect of e-waste is that it is also a valuable secondary resource because it contains copper, gold, silver, palladium, and rare earth elements that can be recovered through eco-friendly recycling methods. Thus, good e-waste management can offer dual benefits: it cuts down on pollution and carbon emissions by making us less reliant on energy-intensive primary resource extraction. This review looks at how e-waste recycling can help reduce pollution and carbon emissions from e-waste at the same time. The review focuses on the lifecycle assessments (LCA), Extended Producer Responsibility (EPR), and new recycling technologies like automated sorting, bioleaching, and electrochemical metal recovery. It also highlights public awareness of recycling, runs awareness campaigns, and makes informal recycling sectors more official in order to promote sustainable practices. Proper e-waste management can thus help to build a circular economy, create social and economic benefits, and help the world meet its climate goals through the combination of new technologies, strong regulations, and community involvement. The composite of these strategies can turn e-waste from a problem for the environment into something that helps the environment and makes it stronger.